Reducing Health Inequalities in Aging Through Policy Frameworks and Interventions - Frances A. S. MacGuire (Frontiers Media S.A., 2020)
Lifepath, a European Commission Horizon 2020 programme of research adopted a life course approach to understanding the impacts of socioeconomic differences on healthy aging and considered the relative importance of lifetime effects by comparing studies on childhood and adult risks. A key component of the programme was the identification of policy relevant results and messages. Longitudinal European cohorts of over 1.7 million individuals from 48 independent cohort studies were harmonized and followed for the key outcomes of mortality and functional decline. Biological markers, allostatic load, and DNA methylation were also examined to help unravel the impact of socioeconomic factors including education, occupation, or income on aging. It is well-recognized that socioeconomic position affects behaviors such as smoking, high alcohol consumption, low physical activity, and a diet low in fruit and vegetables. Lifepath indicated that socioeconomic status is an independent risk factor for death and disease but that it also helps drive the uptake of these well-recognized risk behaviors. The evidence from Lifepath points to a suite of possible policies, some universal, some targeted but it was not possible to assess specific interventions, other than conditional cash transfers, or to explore how interventions might be effective in reducing health inequalities in aging. Nevertheless, it was clear that the timing of interventions is important as the consequences of early interventions may span the whole life course. These influences have important implications for policy making, since appropriate policies can reverse the embodiment of socioeconomic disadvantage, thus reducing health inequalities and resulting in healthier aging. Applying principles of proportional universalism as one approach to reducing inequalities should be considered.